Covalent Organic Frameworks (COFs) for Cancer Therapeutics - Guan, Qun; Zhou, Le‐Le; Li, Wen‐Yan; Li, Yan‐An; Dong, Yu‐Bin (Chemistry : a European journal, 2020)
As newly emerged crystalline porous materials, covalent organic frameworks (COFs) possess fascinating structures and some specific features such as modularity, crystallinity, porosity, stability, versatility, and biocompatibility. Besides adsorption/separation, sensing, catalysis, and energy applications, COFs have recently shown a promise in biomedical applications. This contribution provides an overview of the recent developments of COF‐based medicines in cancer therapeutics, including drug delivery, photodynamic therapy (PDT), photothermal therapy (PTT), and combined therapy. Furthermore, the major challenges and developing trends in this field are also discussed. These recent developments are summarized and discussed to help encourage further contributions in this emerging and promising field. Magic bullet: In this minireview, recent advances in the field of covalent organic frameworks (COFs) for cancer therapeutic applications are highlighted, including those for drug delivery, phototherapy, and combined therapy.